An Adult Case of Kawasaki Disease in a Pregnant Japanese Woman: A Case Report - Kyoko Kanno; Hiroyuki Sakai; Masahide Nakajima; Akira Satake; Takayuki Konishi; Hajime Iizuka (Karger Publishers, 2011)
Kawasaki disease is an acute febrile disease predominantly seen in young children. We report a case of Kawasaki disease in a 32-year-old pregnant woman. She developed a generalized erythematous skin rash accompanied by high fever. Bilateral conjunctival congestion, tender cervical lymphadenopathy, an edematous lower lip and peripheral edema followed by desquamation were observed. She was successfully treated with aspirin and intravenous gammaglobulin (1 g/kg/day). Her course was not complicated by coronary artery aneurysm and she delivered a healthy baby. To the best of our knowledge, this is the first case of Kawasaki disease in a pregnant woman. We suggest that Kawasaki disease should be included in the differential diagnosis of a generalized, erythematous skin rash accompanied by high fever in adults.